Fecal calprotectin concentration in neonatal necrotizing enterocolitis - Jung Min Yoon; Ju Yi Park; Kyung Ok Ko; Jae Woo Lim; Eun Jeong Cheon; Hyo Jeong Kim (Korean Pediatric Society, 2014)
PurposeAmong the many factors associated with acute intestinal mucosal infection, numerous studies have proposed the usefulness of fecal calprotectin. The aim of this study was to evaluate the usefulness of fecal calprotectin in the diagnosis of necrotizing enterocolitis (NEC).MethodsWe collected 154 stool samples from 16 very low birth weight and premature newborns at the Konyang University Hospital neonatal intensive care unit or neonatal nursery. The stool samples were collected using the Calprest device, and the fecal calprotectin level was measured with the BÜHLMANN Calprotectin enzyme-linked immunosorbent assay kit.ResultsFecal calprotectin levels were significantly higher in the NEC group than in the non-NEC group (P=0.02). There was a significant positive linear relationship between the fecal calprotectin level and number of days after birth (P=0.00) in the gestational age <26 weeks group. There was a significant negative linear relationship between the calprotectin level and number of days after birth (P=0.03) in the gestational age ≥26 weeks and <30 weeks group. There was no difference in the calprotectin levels according to the type and method of feeding between the NEC and non-NEC groups.ConclusionFecal calprotectin levels were significantly increased in premature infants with NEC. The fecal calprotectin test is a noninvasive, easy, and useful tool for the diagnosis of NEC.